Dash vs Medditeranean Diet: A Comparative Analysis Of Blood Pressure Reduction In Hypertension: A Literature Review - Dimas Agung Prihanggara (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Hypertension is a major global public health problem, and non-pharmacological management through dietary intervention is a key strategy. The DASH diet and the Mediterranean diet are both frequently recommended, but direct comparison of their superiority requires further analysis. This literature review critically compares evidence from five major studies examining the effectiveness of both diets in various clinical contexts. The synthesis shows heterogeneous findings. High-quality randomized controlled trials indicate that the Mediterranean diet combined with salt restriction achieves greater blood pressure reduction than the DASH diet. However, cross-sectional studies among patients already on antihypertensive medication found no significant association for either diet, suggesting a possible pharmacological ceiling effect. Confounding variables such as study population (adults vs. adolescents) and study design (RCT vs. observational) play an important role in interpreting results. In conclusion, both diets effectively lower blood pressure, but the Mediterranean diet shows superiority in specific clinical contexts, particularly when combined with sodium restriction. The Mediterranean diet may also offer more holistic cardiovascular benefits. Optimal dietary choice should be tailored to the patient's clinical profile, therapeutic goals, and overall management context.